2020
DOI: 10.24251/hicss.2020.598
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Implementing an SMS Messaging System to Overcome the Lack of Transmission of HPV Facts in Saudi Arabia

Abstract: Human papillomavirus (HPV) infections are the leading cause of cervical cancer, which kills hundreds of thousands of women around the world. Facts about HPV exist, yet there is a lack of knowledge about it among women who need to know. One factor that limits the spread of knowledge is that HPV is marked by stigma. Another factor is language barriers. The main aim of this research is to develop and implement a "theory of the solution" (Markus, 2014). The solution designed involves a 2-way interactive messaging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In this study, female university students engaged in risky sexual behaviour because they were likely unaware of HPV and its complications. Contrarily, a study conducted in Saudi Arabia revealed that the use of alcohol and drugs may cause students to be involved in unprotected sex and change from one sexual partner to another within a short period [11]. Similarly, a study conducted in Italy revealed that some students engaged in risky sexual behaviour due to peer pressure and financial constraints [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, female university students engaged in risky sexual behaviour because they were likely unaware of HPV and its complications. Contrarily, a study conducted in Saudi Arabia revealed that the use of alcohol and drugs may cause students to be involved in unprotected sex and change from one sexual partner to another within a short period [11]. Similarly, a study conducted in Italy revealed that some students engaged in risky sexual behaviour due to peer pressure and financial constraints [12].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, if tertiary students do not understand the benefits of HPV vaccines, they may also not be able to influence the community; as a result, young children might not be vaccinated against HPV [5]. In other countries, such as Saudi Arabia, HPV is stigmatized, and women are not allowed to talk about reproductive health issues because it is regarded as a taboo [11]. Therefore, women end up not knowing about the HPV and its vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this also provides reminders to patients on their health status and other services (11). In addition, a study about SMS on women infected with Human papillomavirus (HPV) infections indicates effective methods to maintain women's self-efficacy (12).…”
Section: Introductionmentioning
confidence: 99%
“…The results showed a statistically signi cant difference in self-e cacy before and after receiving the text-messages. 10 There are two methods for customized health messages: targeting and tailoring. Message targeting uses customized messages based on the characteristics of a subgroup of an overall population; for example, they would target people with similar lifestyle traits, such as fresh college graduates starting their careers or people who live in a certain geographical area.…”
mentioning
confidence: 99%